S130 The prevalence of undiagnosed copd on spirometry and emphysema on low-dose ct scans in a lung cancer screening demonstration pilot: a teachable moment?. (15th November 2016) - Horst, C; Ruparel, M; Quaife, S; Ahmed, A; Taylor, M; Bhowmik, A; Burke, S; Shaw, P; McEwen, A; Waller, J; Baldwin, DR; Navani, N; et al.
Abstract : Introduction and objectives: Chronic obstructive pulmonary disease (COPD) and emphysema are considerably under-diagnosed conditions. Low dose CT (LDCT) for lung cancer screening, if implemented, may provide an opportunity for earlier diagnosis of smoking-related conditions, in addition to lung cancer. Data gathered in a lung cancer screening demonstration pilot was analysed to look at COPD-related radiological changes and their relationship with patients' pre-existing diagnoses, spirometry results and smoking status. The aims were to better understand these interlinked conditions and identify the potential for earlier diagnosis and management of smoking cessation interventions for these conditions. Methods: Data were collected as part of the Lung Screen Uptake Trial. Smokers and recent former smokers (quit <5 years) aged 60–75 were invited to a 'lung health check' via their general practitioner (GP). Data on pre-existing diagnoses, smoking status and pre-bronchodilation spirometry, categorised according to the National Institute for Clinical Excellence (NICE) criteria, were collected. Patients who met the eligibility criteria for screening went on to have LDCT. Results were analysed for frequencies, and confidence intervals calculated for the most significant results. Results: 275 patients responded to an invitation to attend a 'lung health check' in the first six months of recruitment. 149 (54.2%) had values consistent with COPD on spirometry. 106 [71.1%, (95% CI: ± 7.3%)] of these individuals were not aware of a diagnosis of COPD, and 81 (76.4%) were current smokers (Figure 1). Of the 103 individuals who had emphysema and no suspicious lesion on LDCT, 74 [71.8%, (95% CI: ± 8.7%)] were not aware of a diagnosis of COPD or emphysema. 55 (74.3%) of these were current smokers, and 33 (44.6%) had preserved spirometry (Table 1 ). Conclusion: Our data demonstrate the considerable burden of undiagnosed COPD in at-risk groups (38.5% of all screened individuals), and show the prevalence of emphysematous change in those patients without a pre-existing, self-reported diagnosis of COPD or with preserved spirometry. Early diagnosis and CT evidence of smoking damage may provide the opportunity to co-implement supportive smoking cessation interventions, earlier medical intervention and prevention of further progression of disease through improved management of these conditions.